Stress and Burnout Amidst Covid-19 Pandemic and its Influence on Job Satisfaction among Staff Nurses in Jolo, Sulu, Philippines - Pangandaman, Hamdoni K.; Isnani-Asak, Nasra U. (Critical Medical and Surgical Nursing Journal, 2024)
Introduction: The global healthcare sector, especially the nursing profession, has experienced heightened demand due to the COVID-19 pandemic, leading to increased job-related stress, elevated burnout rates, and varying levels of job satisfaction that can significantly impact the effectiveness of responses to the pandemic. This study aimed to describe and analyze stress and burnout among nurses in Sulu, and explore how these factors relate to their job satisfaction during the COVID-19 pandemic.Methods: The study employed a descriptive predictive research design to outline the variables and examine their potential impact on job satisfaction. It was conducted at two selected hospitals in Sulu, with nurses as the respondents. The sample comprised 83 staff nurses chosen from a total of 183. Data were collected using a validated and reliable adapted questionnaire. Analysis was carried out with SPSS version 24, including frequency and percentage distribution, mean, standard deviation, and simple linear regression.Results: The study finds that staff nurses' job satisfaction during the COVID-19 pandemic is significantly impacted by age and income, while higher stress levels and moderate burnout negatively affect it. The average mean stress level is 0.929, indicating that stress is rarely experienced, while burnout has an average mean of 1.536, suggesting it is also infrequent. Overall, the average mean job satisfaction score is 0.929, reflecting a general level of satisfaction among the staff nurses.Conclusion: This study concludes that young nurses are essential during pandemics due to their high activity levels but require guidance from experienced professionals to ensure quality healthcare. Administrators should support all nurses and offer reasonable income to manage stress and burnout, impacting job satisfaction. Future research should include a diverse range of healthcare professionals to explore stress and burnout differences among various roles and specializations.